Women and their couple’s behavior regarding birth control - Marques Ferrei, Maria de Lourdes da Silva; Gonçalves, Ivana Regina; Temer Jamas, Milena (Investigación y Educación en Enfermería, 2010)
Objective. To describe women behavior regarding birth control and analyze if such behavior has any cultural influence. Methodology. Qualitative study in which patients were women who were waiting for their family health program consult in three health units of the city Ilah Comprida in Sao Paulo, Brazil. Data were collected during October and November of 2007, the interview was used as source of information, subsequently they were subjected to the content analysis technique. Results. Women are responsible for birth control; they consider there are difficulties with birth control especially due to inefficient information about methods of contraception and family influence over this adopted behavior. Conclusion. Birth control is influenced by cultural models, moral, social and religious values related with the exercise of sexuality.